2021
DOI: 10.1182/blood-2021-153733
|View full text |Cite
|
Sign up to set email alerts
|

PRMT5 Inhibition Promotes FOXO1 Tumor Suppressor Activity to Drive a Pro-Apoptotic Program That Creates Vulnerability to Combination Treatment with Venetoclax in Mantle Cell Lymphoma

Abstract: Mantle cell lymphoma (MCL) is an incurable B cell malignancy, comprising 5% of non-Hodgkin lymphomas diagnosed annually. MCL is associated with a poor prognosis due to emergence of resistance to immuno-chemotherapy and targeted agents. The average overall survival of patients with MCL is 4-6 years and for the majority of patients who progress on targeted agents, survival remains at a dismal 3-8 months. There is a major unmet need to identify new therapeutic approaches that are well tolerated to improve treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“… 56 In mantle cell lymphoma (MCL), it has been reported that genomic regions of BAX and multiple other pro-apoptotic BCL2 family proteins are bound by FOXO1. 57 The authors further demonstrated that disruption of FOXO1 activity sensitized MCL cell lines to venetoclax. However, the relationship between FOXO1 activity and venetoclax resistance has not been investigated in AML.…”
Section: Resultsmentioning
confidence: 95%
“… 56 In mantle cell lymphoma (MCL), it has been reported that genomic regions of BAX and multiple other pro-apoptotic BCL2 family proteins are bound by FOXO1. 57 The authors further demonstrated that disruption of FOXO1 activity sensitized MCL cell lines to venetoclax. However, the relationship between FOXO1 activity and venetoclax resistance has not been investigated in AML.…”
Section: Resultsmentioning
confidence: 95%
“…Inhibition of bromodomain extra-terminal (BET) proteins, histone deacetylases (HDACs) or protein arginine methyltransferases (PRMT5) affect expression of BCL-X L , MCL-1 and BIM and synergize in vitro and in MCL mouse models with venetoclax (Fig. 4 ) [ 83 86 ]. Phase I clinical trials of the combination of venetoclax and the BET inhibitor R06870810 or the dual HDAC and PI3K inhibitor fimepinostat (CUDC-907) in R/R DLBCL showed manageable safety profiles and durable anti-tumor activities [ 87 , 88 ], but in MCL no clinical trials have been initiated yet.…”
Section: Strategies To Overcome Primary and Secondary Venetoclax Resi...mentioning
confidence: 99%
“…Venetoclax blocks BCL2 from sequestering factors that activate pro-apoptotic BCL2 family proteins, such as BAX 60 . In mantle cell lymphoma (MCL), it has been reported that genomic regions of BAX and multiple other pro-apoptotic BCL2 family proteins are bound by FOXO1 61 . The authors further demonstrated that disruption of FOXO1 activity sensitized MCL cell lines to venetoclax.…”
Section: Foxo1 Transcription Factor Activity Mediates Venetoclax Resi...mentioning
confidence: 99%